Aspectos fenológicos e consumo alimentar de Cornops Aguaticum (Bruner, 1906) (Orthoptera: Acrididae: Lepnsminae) associado a Eichhornia Crassipes (Mart.) Solms (Pontederiaceae) em dois lagos da Amazonia Central, Brasil - Braga, Carlos Elias De Souza (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
The semi-aquatic neotropical grasshopper Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae) lives associated with the aquatic macrophyte Eichhornia crassipes (MaFt.) Solms (Pontederiaceae) ("water hyacinth") on which it feeds. Phenological aspects of adults and nymphs were studied and their feeding consumption was measured in order to evaluate the potential of this grasshopper for the biological control of E. crassipes, considering the hydrological regime of the Central Amazon. The study was executed in Camaleão Lake (03°15'S, 5g058'W) on Marchantaria Island, and Janauari Lake (03°12'29"S, 60°01'53'W), both in the municipality of Iranduba, Amazonas, Brazil. For phenological study 17 mdfithly excursions were realized (Apri112006 to August12007) to the study lakes, using an entomological net adapted for the caption of grasshoppers (70 cm in diameter and 100 cm of sack collector). The feeding consumption in the field was determined by leaf area analysis and biomass of the plants (gramslfresh weight) in experiments undertaken between April and August 2007. In these experiments grasshoppers were placed in screened cages (60 x 60 x 80 cm and 1 mm net mesh) together with the host plant, at three different densities: (a) minor density (8 grasshoppers); (b) major density (32 grasshoppers), and (c) control group (without grasshoppers). For phenological study, 1700 individuals were captured (602 adults and 1098 nymphs), comprising 850 specimens for each lake studied. The abundance and biomass of adults and nymphs of C. aquaticum, as well as the period of the development of nymphs, are closely related to the oscillation of river water levels. First instar nymphs were found throughout the whole sample period (n = 176 in Camaleão Lake; n = 232 in Januari Lake), and females were present in almost all months of the sample period (n = 61 in Camaleão Lake; n = 37 in Janauari Lake), as were females with type III eggs (mature eggs). This demonstrates that reproduction of these grasshoppers is continuous during the year with a tendency of high reproduction peaks during the high water period. In feeding consumption experiments the control of E. crassipes by the grasshopper was positive, where control efficiency was more evident at higher grasshopper densities. Reduction in leaf area of the macrophyte was greater than 90%, although control was less perceptible in biomass measurements.The inundation pulse of the Amazon River constitutes the principal factor that influentes the population dynamics of C. aquaticum. Water levels indirectly influence the grasshopper population and directly affect host macrophyte. The grasshopper C. aquaficum can be considered to be an efficient agent for the biological control of E. crassipes, however, the phenological plasticity of the grasshopper, as well as that of the host plant in relation to the environment where they are found, should be considered and evaluated before using C. aquaticum as a control agent against this invasive aquatic macrophyte.
Keywords: Cornops Aquaticum; Eichhornia Cassipes